Hydrodynamics of Non‐Equilibrium Soil Water Retention - Itai Einav; Mario Liu (Water Resources Research)
Abstract Water retention in soil exhibits diverse phenomena, including suction‐saturation hysteresis, non‐unique air entrapment at zero suction and negative suction under partial saturations. The constancy of suction after a long rest can be broken by relatively minor mechanical or hydraulic agitations such as low‐amplitude wetting cycles—this fact is here being related to metastable states that differ from the true equilibrium. The complete suction‐saturation relationships are thus being recovered using non‐equilibrium Landau's hydrodynamic theory and Onsager's reciprocity principles. Equilibrium suction does not pertain to hysteresis, yet can be approached through small amplitude agitations over long duration. Conditions for rate independence are being described, while rate‐dependency are also accommodated and illustrated. Finally, it is shown that the new non‐equilibrium theory retains the rigorously derived equilibrium result of the effective stress of partially saturated soils.